The influence of whole body cryotherapy on plasma concentration of melatonin and serotonin in patients with osteoarthrosis of the lumbar spine - MARTA BARŁOWSKA-TRYBULEC; JOANNA SZKLARCZYK; JOLANTA JAWOREK (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2021)
Background: ‪Osteoarthrosis (OA) is the most common disease affecting mankind. There are many physiotherapeutic methods of treating OA symptoms. One of them is whole body cryotherapy (WBCT). The aim of this study was to present the impact of WBCT combined with kinesiotherapy on functional efficiency and changes in plasma concentrations of serotonin and melatonin in patients with lumbar spine OA.. Material and methods: ‪60 patients underwent a series of WBCT combined with kinesiotherapy (group A). 60 patients underwent a series of kinesiotherapy alone (group B). Before and after the therapy patients were examined by Rolland Morris Disability Questionnaire (RMDQ), and blood samples were collected for laboratory assessment. Results: ‪Following therapy, the functional efficiency (RMDQ) improved by 33% in both study groups (p < 0.0001). After the therapy, both in the group of patients undergoing WBCT combined with exercises (group A, p = 0.032) and the cryotherapy alone (group B, p < 0.0001), the plasma melatonin concentration significantly increased. The rise of plasma serotonin concentrations was higher in group B as compared to group A, but in both study groups the increase in plasma serotonin was statistically significant (p < 0.0001).. Conclusions: ‪WBCT combined with therapeutic exercises as well as kinesiotherapy used alone resulted in an increase in melatonin and serotonin plasma levels and an improvement in functional efficiency in patients with lumbar spine OA.